1H NMR studies of molecular interaction of D-glucosamine and N-acetyl-D-glucosamine with capsaicin in aqueous and non-aqueous media. (27th November 2017) - Higuera-Ciapara, Inocencio; Virués, Claudia; Jiménez-Chávez, Marcela; Martínez-Benavidez, Evelin; Hernández, Javier; Domínguez, Zaira; López-Rendón, Roberto; Velázquez, Enrique F.; Inoue, Motomichi
Abstract: Complex formation of D-glucosamine (Gl) and N -acetyl-D-glucosamine (AGl) with capsaicin (Cp) were studied by 1 H NMR titrations in H2 O-d2 and DMSO-d6 ; capsaicin is the major bioactive component of chili peppers. Every titration curve has been interpreted by formulating a suitable model for the reaction equilibrium, to elucidate intermolecular interactions. In DMSO, glucosamine cations associate with each other to yield linear aggregates, and undergo pseudo -1:1-complexation with capsaicin, the formation constant being ca . 30 M −1 . N -Acetylglucosamine, without self-association, forms a 2:1-complex AGl2 Cp with the stability of ca . 70 M −2 . These complexations are achieved by intermolecular hydrogen bonds. In D2 O, glucosamine undergoes reversible protonation equilibrium between Gl 0 and GlH + with the logarithmic protonation constants log K D  = 8.63 for α-glucosamine and 8.20 for β-isomer. Both anomeric isomers of deprotonated glucosamine form Gl 0 Cp-type complexes of capsaicin, in a competitive manner, with a formation constant of 1040 M −1 for the α-glucosamine complex and 830 M −1 for the β-complex; the anomeric carbons result in the difference in thermodynamic stability. The reactant molecules are closed up by the solvent-exclusion effect and/or the van der Waals interaction; the resulting pair is stabilized by intermolecular hydrogen bonding within a local water-free space between the component molecules. By contrast, neither protonated glucosamine (GlH + ) nor N -acetylglucosamine yields a capsaicin complex with the definite stoichiometry. The monosaccharides recognize capsaicin under only a controlled condition; the same phenomena are predicted for biological systems and nanocarriers based on polysaccharides such as chitosan. Graphical abstract: Highlights: Interaction of glucosamine with capsaicin is sensitive to pH and solvent. Glucosamine forms a stable 1:1-complex with capsaicin in basic aqueous media. The capsaicin complex of anomeric α form is more stable than the β complex. N -Acetylglucosamine is less reactive with capsaicin than glucosamine in water.